Enhanced MALDI-TOF MS Analysis of Phosphopeptides Using an Optimized DHAP/DAHC Matrix - Junjie Hou (Journal of Biomedicine and Biotechnology, 2010)
Selecting an appropriate matrix solution is one of the most effective means of increasing the ionization efficiency of phosphopeptides in matrix-assisted laser-desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). In this study, we systematically assessed matrix combinations of 2, 6-dihydroxyacetophenone (DHAP) and diammonium hydrogen citrate (DAHC), and demonstrated that the low ratio DHAP/DAHC matrix was more effective in enhancing the ionization of phosphopeptides. Low femtomole level of phosphopeptides from the tryptic digests of α-casein and β-casein was readily detected by MALDI-TOF-MS in both positive and negative ion mode without desalination or phosphopeptide enrichment. Compared with the DHB/PA matrix, the optimized DHAP/DAHC matrix yielded superior sample homogeneity and higher phosphopeptide measurement sensitivity, particularly when multiple phosphorylated peptides were assessed. Finally, the DHAP/DAHC matrix was applied to identify phosphorylation sites from α-casein and β-casein and to characterize two phosphorylation sites from the human histone H1 treated with Cyclin-Dependent Kinase-1 (CDK1) by MALDI-TOF/TOF MS.